2017
DOI: 10.1080/09513590.2017.1290073
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor (BDNF) plasma concentration in patients diagnosed with premature ovarian insufficiency (POI)

Abstract: Premature ovarian insufficiency (POI) is defined as a cessation of function of ovaries in women younger than 40 years old. Brain-derived neurotrophic factor (BDNF) is a protein critically involved in neuronal growth and metabolism. BDNF also has been shown to be important regulator of oocyte maturation. Recent data show that BDNF can be potentially involved in POI pathology. The aim of the study was to assess the BDNF plasma concentrations in patients diagnosed with idiopathic POI. 23 women diagnosed with POI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…The mean value of serum progesterone showed lower significant difference in POI cases when compared with healthy control. The present was in agreement with that reported by Czyzyk, Adam, et al (28) and Bemardi, F., et al (29) . The low serum levels of progesterone and estradiol may be attributed to failure of the ovary to produce them.…”
Section: Discussionsupporting
confidence: 94%
“…The mean value of serum progesterone showed lower significant difference in POI cases when compared with healthy control. The present was in agreement with that reported by Czyzyk, Adam, et al (28) and Bemardi, F., et al (29) . The low serum levels of progesterone and estradiol may be attributed to failure of the ovary to produce them.…”
Section: Discussionsupporting
confidence: 94%
“…BDNF, a member of the neurotrophin growth factors family, could promote oocyte maturation and embryo development and was also associated with infertility and endometriosis 29‐32 . Czyzyk et al 33 found lower plasma BDNF level in overt POI patients (FSH > 40 IU/L). Different stage of disease, sample source, and small sample size might explain the data inconsistence.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, with quite smaller sample size, only focused on overt POI patients with FSH > 40 IU/L but not bPOI patients at earlier stage. Moreover, those studies detected cytokines in sera but seldom involving cytokines in follicular fluids 33,45 . In addition, it is generally not the presence or absence of any one cytokine that is responsible for the resultant immune response, rather the collective effect of the “cytokine milieu,” or cytokine microenvironment surrounding the effector cell.…”
Section: Discussionmentioning
confidence: 99%
“…In clinics, POF patients seldom undergo surgery. Here the young (ages [29][30][31][32][33][34][35] and aged (61-64) female groups were used as the high-and low-fertility group respectively. It is generally believed that the follicle number is dramatically reduced after menopause.…”
Section: Resultsmentioning
confidence: 99%
“…All these phenotypes are very similar to those seen in women with POF 25 . In humans, the plasma level of BDNF is decreased in POF patients 34 . Genome-wide association studies (GWAS) analysis have revealed a genetic association between Bdnf (11p14.1) and POF 35 .…”
mentioning
confidence: 99%